Territory in urban food policies: the case of Spain - Henar Pascual; Juan Carlos Guerra (Frontiers in Sustainable Food Systems, 2024)
Over the last few decades, cities have taken on an active role in the formulation of food policies in line with the transition toward local, sustainable food systems. These policies have been materialized through the formulation of systemic, holistic urban food strategies. By setting up spatial, relational and organizational proximity circuits, they aim to reconnect the places involved in the production and consumption of food within the territory. The objective is to do so by interaction between the networks of actors on the different geographical scales. This article analyzes the food policies of six Spanish cities that signed the Milan Urban Food Policy Pact. Barcelona, Madrid, Valencia, Vitoria, Valladolid and Zaragoza have fulfilled their promise by formulating food strategies that set out their commitment to the construction of new, urban food systems that reconsider, from a territorial perspective, the relationship between the city and food. Using a conceptual framework that spans two well-known theoretical systems (the local territorial systems (LoTS) and the sustainable food networks (SFN)); a systematic review of the documents generated in the formulation of the urban food policies is carried out. The territorial capital linked to food is examined; the systems of actors that make up the food strategies are identified; the models of governance that the said strategies deploy and their capacity for self-organization are typified; and the potential of the public agendas for encouraging the construction of localized alternatives and the territorial sustainability of the urban food systems are evaluated. The results suggest that the Spanish urban food strategies, although conceptually inspired by the principles of the Milan Pact, are still far from possessing similarly transformative capacities. Such capacities are directly linked to the characteristics of the place: the existence of relational goods connected to food, the attributes of the territorial food capital, the density of the social capital, and the culture of the territorial planning. Beyond the generic references to the commitment to food, it is the context that determines its personality and reach, the solidity of the food governance, and the political sustainability of the processes that one wishes to set up.